Effects of just-in-time inquiry prompts and principle-based self-explanation guidance on learning and use of domain texts in simulation-based inquiry learning - Fukuda, Mari; Nesbit, John C.; Winne, Philip H. (Frontiers in Education, 2024)
Although scientific inquiry in simulation may enhance learning, learners often face challenges creating high demand for self-regulation due to an abundance of information in simulations and supplementary instructional texts. In this research, participants engaged in simulation-based inquiry about principles of electric circuits supplemented by domain-specific expository text provided on-demand. They received just-in-time inquiry prompts for inquiry behaviors, guidance to self-explain electrical principles, both, or neither. We examined how these interventions influenced participants’ access of text information and achievement. Undergraduates (N = 80) were randomly assigned to one of four groups: (1) inquiry prompts and principle-based self-explanation (SE) guidance, (2) inquiry prompts without principle-based SE guidance, (3) principle-based SE guidance without inquiry prompts, or (4) control. Just-in-time inquiry prompts facilitated learning rules. However, there was no main effect of principle-based self-explanation guidance nor an interaction involving both interventions. Effects of just-in-time inquiry prompts were moderated by prior knowledge. Although principle-based self-explanation guidance promoted re-examination of text-based domain information, reading time did not affect posttest scores. These findings have important implications for instructional design of computer-based adaptive guidance in simulation-based inquiry learning.